Does hope morally vindicate faith? - Jeffreys, Anne (International journal for philosophy of religion, 2017)
Much attention in philosophy of religion has been devoted to the question of whether faith is epistemically rational. But is it morally and practically permissible? This paper explores a response to a family of arguments that Christian faith is morally impermissible or practically irrational, even if epistemically justified. After articulating the arguments, I consider how they would fare if they took seriously the traditional notion that genuine faith is always accompanied by Christian hope. I show how the norms of hope regulate Christian faith in such a way that it does not involve, and certainly does not entail, the morally and practically problematic attitudes and behaviors with which it is associated.